Disaster Media Effects: A Systematic Review and Synthesis Based on the Differential Susceptibility to Media Effects Model. (25th May 2018) - Houston, J Brian; Spialek, Matthew L; First, Jennifer
Abstract: Natural and human-caused disasters receive extensive media coverage that often includes images, video, and descriptions of death, injury, and destruction. Individual exposure to disaster media has been found to be associated with a variety of effects (e.g., mental health reactions) among children and adults in numerous studies. Despite evidence of disaster media effects, the literature is not well organized. To improve integration, we conducted a systematic review and used the Differential Susceptibility to Media Effects Model (DSMM) to organize results. We analyzed 66 studies, representing 78, 643 participants, and found that the disaster media effects literature is built upon the theory of psychological trauma, that the role of uncertainty and social aspects of disaster media effects are understudied, and that transactional disaster media effect studies are nonexistent. Our analysis also indicates that adding a contextual category to the DSMM model is beneficial in synthesizing media effects. Opportunities for future research are discussed.